Study of efficacy of skin grafting in healing lower extremity ulcers in a rural tertiary care hospital - P., Akshatha A.; Mohan, Ambikavathy; S., Kailashnath B. (International Surgery Journal, 2022)
Background: Ulcers are discontinuity of skin/mucous membrane. Chronic ulcers are caused by skin loss that takes long to heal. Skin grafting helps tissue regeneration, hastens healing process. Skin grafts are classified as Split-thickness skin grafts and full-thickness skin grafts. STSG consist of epidermis and some layers of dermis. FTSG consists of epidermis, dermis, and subcutaneous tissue. Methods: This retrospective and prospective study was conducted on 80 patients diagnosed with healing ulcers of the lower extremity admitted and treated at MVJMC and RH from January 2021-August 2021. Inclusion criteria were patients >18 years, both sexes. Exclusion criteria were patients who were having malignant/TB ulcers and children. Results: Data was analysed using SPSS-21. In our study, healing ulcers were seen in 80 patients, of which 48 (60%) males and 32 (40%) females. 4 (5%) patients had venous ulcers, 5 (6.25%) varicose ulcers, 10 (12.5%) post burn ulcers, 22 (27.5%) traumatic ulcers, 6 (7.5%) amputated stump and 33 (41.25%) diabetic foot ulcers. STSG 70 (87.5%) and FTSG 10 (12.5%). The uptake was 70-80% in 11 (13.75%), 80-90% in 20 (25%), 90-99% in 24 (30%) and 100% in 25 (31.25%). Complications observed 4 (5%) infections, 5 (6.25%) no graft uptake and 77 (88.75%) had no complications. Conclusions: Although FTSG can be offered in some cases, STGS is the gold standard in terms of efficacy for healing ulcers. Outcome of the graft depends not only on type of graft also on quality of recipient bed. Skin grafting improves the quality of life in reducing pain.